(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the pivotal role and enduring significance of Eastern thinkers in the historical development of pedagogical thought. The study aims to highlight how the philosophical, ethical, and educational ideas of prominent scholars from the East — such as Al-Farabi, Avicenna (Ibn Sina), Al-Ghazali, Alisher Navoi, and others — have contributed to shaping the foundations of modern educational theory and practice. The research analyzes their views on moral upbringing, intellectual development, the teacher-student relationship, and the purpose of education in forming a harmonious and enlightened individual. By drawing comparisons between classical Eastern pedagogical ideas and contemporary educational concepts, the article reveals that many modern pedagogical principles — including the emphasis on humanism, creativity, moral integrity, and lifelong learning — have deep historical roots in Eastern thought. The study also underlines the relevance of these teachings in the context of today’s global education reforms, particularly in Uzbekistan, where national values and traditions are being harmoniously integrated with modern pedagogical innovations. Furthermore, the research discusses the methodological approaches used by Eastern scholars in the process of teaching and moral education, illustrating how their intellectual heritage continues to inspire educators and researchers worldwide. The article concludes that understanding and reinterpreting the pedagogical legacy of Eastern thinkers is crucial for developing culturally rich, ethically grounded, and forward-looking educational systems.